Indication and outcome of relaparotomy after caesarean section (Bangladesh Medical Journal Khulna, 2013)
The objective was to determine the indicatons, management and the outcome among the patient who underwent relaparotomy after caesarean section and to suggest the way to improve the quality of care. This was a retrospective descriptive study done in a tertiary level referral and teaching hospital, Khulna, Bangladesh, out of 55 cases requiring relaparotomy after caesarean section. Over a period of 15 months from 1st January 2011 to 31st march 2012, 1180 caesarean deliveries were done, out of total 3270 deliveries. During this period, relaparotomy was done in 55 cases. Among these, 10 cases followed caesarean delivery at this institute itself, while 45 cases have had caesarean delivery at peripheral hospitals. Postpartum haemorrhage in 31 cases (56.36%) and rectus sheath haematoma in 8 cases (14.55%) were the leading cause of relaparotomy. Among the 55 cases, 39 had emergency caesarean delivery while 16 had elective operation. Procedures undertaken at laparotomy were hysterectomy in 21 cases (38.18%), resuturing of uterine wound with uterine brace suture in 13 cases(23.63%), bilateral uterine arteries and ovarian vessels ligation in 7 cases (12.73%), drainage of haematoma in 8 cases (14.55%), and repair of anterior abdominal wall & peritoneal toileting in 5 cases (9.09%). A third laparotomy was done in 3 cases of which 2 cases were due to secondary PPH, a negative relaparotomy was done in one case. There were 7 maternal deaths following relaparotomy caused by hemorrhagic shock, septicaemia & renal failure and was 12.73%. Caesarean section is a life saving operation. However maternal mortality and near miss fatality after relaparotomy following caesarean section are common. So, relaparotomy should be considered as a procedure after a near miss fatality of mother. DOI: http://dx.doi.org/10.3329/bmjk.v45i1-2.13625 Bang Med J (Khulna) 2012; 45 : 19-23